2022
DOI: 10.1016/j.optom.2020.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Agreement of wavefront-based refraction, dry and cycloplegic autorefraction with subjective refraction

Abstract: Purpose To evaluate the agreement of dry, and cycloplegic autorefraction and wavefront-based refraction with subjective refraction. Method 83 subjects aged 19–57 years were included in this cross-sectional study. Refractive status was determined using four methods including subjective refraction, wavefront-based refraction, dry and cycloplegic autorefraction. Refractive data were recorded as sphere, cylinder and spherical equivalent (SE). Power vector components were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 48 publications
3
22
0
Order By: Relevance
“…The two refraction methods also overestimated the severity of myopia in similar proportions. Such a shift has been described previously with autorefractometry and retinoscopy, both in clinical- [12][13][14][16][17][18][19][20][21][22] and population-based studies. 14,[23][24][25][26][27][28][29] Specifically, non-cycloplegic refraction has been reported to overestimate the severity of myopia and underestimate that of hyperopia.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…The two refraction methods also overestimated the severity of myopia in similar proportions. Such a shift has been described previously with autorefractometry and retinoscopy, both in clinical- [12][13][14][16][17][18][19][20][21][22] and population-based studies. 14,[23][24][25][26][27][28][29] Specifically, non-cycloplegic refraction has been reported to overestimate the severity of myopia and underestimate that of hyperopia.…”
Section: Discussionsupporting
confidence: 59%
“…Underestimation of positive spherical and both over-and underestimation of spherical negative power by autorefractometry under non-cycloplegic conditions has been reported previously. [12][13][14][15] These studies also showed that non-cycloplegic autorefractometry tended to either underestimate 13,14 or overestimate negative cylindrical power. 12 On the contrary, SE values determined with noncycloplegic retinoscopy and autorefractometry produced more myopic measurements than the same method under cycloplegic conditions.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Thibos et al [17] studied the precision of 33 different metrics derived from the wavefront aberration map of the eye, to predict the spherical equivalent of the refractive error. They found mean absolute differences on the spherical equivalent, compared with the subjective refraction, ranging from 0.25 to 0.48D, giving birth, in 2004, to wavefront autorefractometry, a discipline that has provided several autorefraction technologies over the years [7,10,18,[20][21][22][23][24]. Modern autorefractometers provide mean absolute differences ranging from ±0.55 to ±0.24D, depending on the autorefractometer [20,25].…”
Section: Introductionmentioning
confidence: 99%
“…A recent review [26] analyzed four portable autorefractors and reported that QuickSee provides the lowest mean absolute difference (±0.21D) [27]. Many other studies have compared subjective refraction with different types of autorefractors, reporting similar differences [10,19,2124]. To summarize, both classic autorefraction and wavefront-based autorefraction provide high repeatability, with wavefront autorefractors providing better predictions of the spherical component of the subjective refraction (mean absolute deviations between ±0.25 and ±0.50D).…”
Section: Introductionmentioning
confidence: 99%